Colaboración docente on-line en educación universitaria - Ávila, Rodolfo Esteban; Spinelli, Osvaldo M.; Ferreira, Ana Silvia Sartori Barraviera Seabra [UNESP]; Soñez, Carlos; Samar, María Elena; Ferreira Júnior, Rui Seabra [UNESP] (FapUNIFESP (SciELO), 2011)
Online teaching collaboration allows the creation of virtual communities. Virtual tools in a networked team allow creating virtual classes in different geographic locations. These environments allow knowledge transfer between students and faculty, including synchronous and asynchronous activities. In this article, we describe our experience with online teaching collaboration using virtual tools in university education. The software packages were Skype, an application for voice over Internet (VoIP) and LAN, a virtual digital class available at http://www.cevap.unesp.br/abertura.htm. These media were used on different days and at different locations for webcasting and receiving. The themes were: 1) "How to prepare a videoconference", 2) "The importance of ICTs in university teaching", 3) "Virtual platforms such as automated databases in literature searches", and 4) "Using the virtual laboratory in teaching Cell Biology, Histology, and Embryology". Virtual tools allow online collaboration among teachers at different geographic locations, in addition to training human resources to use such tools in order to improve performance in university education.

La colaboración docente on-line permite la creación de comunidades virtuales. Las herramientas virtuales de un equipo en red permiten crear clases virtuales en diferentes localizaciones geográficas. Estos ambientes permiten, en la Educación, diseñar transferencia de conocimientos entre alumnos y docentes incluyendo actividades sincrónicas y asincrónicas. En el presente trabajo describimos nuestra experiencia en colaboración docente on-line usando herramientas virtuales en educación universitaria. Los programas de conexión utilizados fueron 1- Skype: software de aplicación para llamadas en Internet (VoIP). 2- LAN. Aula virtual digital usando la URL: http://www.cevap.unesp.br/abertura. htm. Con los diferentes medios de comunicación disertó el docente colaborador a distancia en diferentes días y sitios de emisión y recepción. Los temas fueron: 1- "Cómo preparar una videoconferencia", 2- "Importancia de las TIC en docencia universitaria", 3- "Plataformas virtuales como bases de datos automatizadas en la búsqueda bibliográfica". 4- "Uso del laboratorio virtual en la docencia de Biología Celular, Histología y Embriología". Las herramientas virtuales permiten la colaboración on-line de docentes situados en diferentes lugares geográficos y la formación de recursos humanos que usarán los entornos virtuales en el desempeño de la docencia universitaria.

A colaboração docente on-line permite a criação de comunidades virtuais. As ferramentas virtuais de uma equipe em rede permitem criar aulas virtuais em diferentes localizações geográficas. Estes ambientes permitem na educação a transferência do conhecimento entre alunos e docentes, incluindo atividades síncronas e assíncronas. Neste trabalho descrevemos nossa experiência em colaboração docente on-line, utilizando ferramentas virtuais na educação universitária. Os softwares utilizados foram 1-Skype: Software de aplicação para chamadas na Internet (VoIP). 2- LAN: Aula virtual digital disponibilizado em http://www.cevap.unesp.br/abertura.htm. Estas mídias foram utilizadas em dias e locais de transmissão e recepção diferentes. Os temas foram: 1- "Como preparar uma videoconferência", 2- "Importância das TICs na docência Universitária", 3- "Plataformas virtuais com bases de dados automatizadas na busca bibliográfica", 4- "Uso do laboratório virtual no ensino de Biologia Celular, Histologia e Embriologia". As ferramentas virtuais permitem a colaboração on-line de docentes localizados em diferentes localizações geográficas, além de formar recursos humanos que as usarão para melhorar o desempenho da educação universitária.
Online teaching collaboration in university education
Colaboração docente online na educação universitária
Keywords: Medical education; Virtual teaching; Virtual tools; Educación médica; Docencia virtual; Herramientas virtuales; Educação de graduação em medicina; Educação virtual; Ferramentas virtuais